Influence of different sintering temperature on mechanical behavior of alumina (AL2O3) reinforced aluminum metal matrix composite (Al MMC) - Ahmad Fadli, Ahmad Sanusi (2008)
This research focused on the study of the influence of different sintering temperature of physical and mechanical behaviour of Aluminum Metal Matrix Composites (Al MMC) reinforced with alumina (Al2O3). Al MMC reinforced with rigid ceramic particulates have become increasingly important for structural applications in aerospace, automotive and other transport industries, because of their high specific strength and modulus, good wear resistance as well as ease of processing. In this project, the influence of sintering temperature was investigated on its hardness and microstructure. These Al MMCs have been traditionally fabricated by powder metallurgy (PM) method. There are three main steps in PM which are blending, compacting and sintering. The experiments were performed on 10% weight percentage of Al2O3 on different sintering temperature. In this study, five specimens of the composite were sintered with different temperature which are 400 0C, 450 0C, 500 0C, 550 0C, and 600 0C. Then, the influence of different sintering temperature on physical and mechanical behavior of the composite was studied. The specimens were investigated on their hardness and microstructure. The hardness of the composites was examined using Vickers Hardness Test and Image Analyzer was used to study the microstructure of the composite. The result shows that the hardness of the composite decreased with the increasing of sintering temperature. Then from the microstructure observation, the grains of alumina increased when the sintering temperature increased. Furthermore, the result of this study also was compared with the other published work, and it shows the correlation each other.